212 Visual, Salience and Motor Networks Are Related to Tremor Recovery After Stereotactic Radiosurgical Thalamtomy: A Resting-State fMRI Study. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Tuleasca, Constantin; Regis, Jean; Najdenovska, Elena; Witjas, Tatiana; Girard, Nadine; Champoudry, Jerome; Thiran, Jean-Philippe; Cuadra, Meritxell Bach; Levivier, Marc; Van de Ville, Dimitri
Abstract: INTRODUCTION: Essential tremor (ET) is the most common movement disorder. Drug-resistant ET can benefit from standard procedures (deep brain stimulation, thalamotomy) or minimally invasive high-intensity focused ultrasound (HIFU) or stereotactic radiosurgical thalamotomy (SRS-T). Resting state fMRI (rs-fMRI) is a noninvasive imaging method acquired in absence of a task. We examined whether rs-fMRI correlates with tremor score on the treated hand (TSTH) improvement 1 yr after SRS-T. METHODS: We included 17 consecutive patients treated with left unilateral SRS-T in Marseille, France. Tremor score evaluation and rs-fMRI were acquired at baseline and 1 yr after SRS-T. Resting-state data (34 scans) were analyzed without a priori hypothesis, in Lausanne, Switzerland. Based on degree of improvement in TSTH, to consider SRS-T at least as effective as medication, we separated 2 groups: 1, < =50% (n = 6, 35.3%); 2, >50% (n = 11, 64.7%). They did not differ statistically by age ( P  = .86), duration of symptoms ( P  = .41), or lesion volume at 1 yr ( P  = .06). RESULTS: We report TSTH improvement correlated with interconnectivity strength between salience network with left claustrum and putamen, as well as between bilateral motor cortices with right visual association area (the former also with lesion volume). Longitudinal changes showed additional associations in interconnectivity strength between right dorsal attention network with ventro-lateral prefrontal cortex and salience network with fusiform gyrus. CONCLUSION: Brain functional connectivity measured by rs-fMRI relates to clinical response after SRS-T. Relevant networks are visual, motor, and attention. Interconnectivity between visual and motor areas is a novel finding, revealing implication in movement sensory guidance.